Paper-based approach for cancer biomarker MMP7 detection using quantum dots and molecularly imprinted polymers - Oliveira, Pedro (2024)
(Introduction) Preliminary investigation using lab-on-paper Molecular Imprinted Polymers (MIPs) paired with Quantum Dots (QDs) to detect Matrix Metalloproteinase-7 (MMP7) using image processing to quantify fluorescence and area with a CMOS sensor reflex camera. MMP7 is critical in pancreatic tumor formation, which has the lowest survival rate among malignant malignancies. High levels of the MMP7 in blood have been associated to a poor prognosis and limited survival in patients. CdTe Quantum Dots (CdTe@MPA QDs) are luminescent nanoparticles with narrow emission spectra, enabling for exceptional sensitive detection of biomarkers.Combination of MIPs with CdTe MPA-capped provide selectivitive for biomiarker.